Recent Developments in the Field of Carbon Fibers - Rita Khanna; Romina Cayumil (IntechOpen, 2018)
Carbon fibres are lightweight, chemically stable materials with high mechanical strength, and have state-of-the-art applications in aerospace, marine, construction and automotive sectors. The demand for carbon fibre?based components is expected to grow dramatically with expanding opportunities for lightweight metals and composites. Although this field has achieved a high level of maturity, nanoscale developments in carbon fibres have seen dramatic improvements in the functions of conventional biomaterials and composites. This book reveals several new developments in the field to enhance characteristics of carbon fibres and their composites, novel applications for tissue engineering, biological scaffoldings and implants, recycling and reuse of end-of-life CFRP and manufacturing waste and other issues of concern in the field of carbon fibres.
English
Keywords: Composite Materials; Physical Sciences; Engineering and Technology; Materials Science